Mejoramiento y mantenimiento electromecánico del banco de pruebas de ensayos a torsión, para prácticas en el laboratorio de la UAN sede Villavicencio (2023)
The project consists of improving and performing electromechanical maintenance on the torsion test bench used in the laboratory of Antonio Nariño University - Villavicencio campus, in order to guarantee its correct functioning and prolong its useful life. Additionally, the intention is to improve laboratory practices for students and facilitate research in the field of materials mechanics. This update will allow for more precise and efficient tests in the laboratory through electromechanical maintenance, replacement of damaged parts and components, implementation of a graphical interface to visualize test results, and generation of electrical diagrams to facilitate equipment use by students and teachers. This translates into better training for students and higher quality results in the research carried out at UAN. Ultimately, this is an intervention and investment that adds value and improves the laboratory's ability to continue training future professionals Keywords: Torsion, test bench, PLC, maintenance, improvement, electromechanical.